The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1149/1945-7111/acb8e2
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofiber Electrodes for High and Low Humidity PEMFC Operation

Abstract: MEAs with nanofiber mat electrodes containing Pt/C catalyst and Nafion binder were fabricated and evaluated. The electrodes were prepared by electrospinning a solution of catalyst powder, salt-form Nafion (with Na+, Li+, or Cs+ as the sulfonic acid counterion), and a carrier polymer of either polyethylene oxide or poly(acrylic acid). The carrier polymer was extracted prior to MEA testing by a hot water soaking step. The resulting fibers were 15-17% porous, with a core-shell-like morphology (a coating of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The reason could be the presence of nmsized pores within the bers by the extraction of PAA carrier polymer-trapped water via capillary condensation, showing a similar voltage trend to PCL electrodes. 30 This suggests that although NFCL has different pore distributions from PCL, the difference in pore distribution did not inuence the cell performance as expected. It demonstrates a weak inuence of the nanober mat pore structure on performance, consistent with the conclusion drawn from LCD results.…”
Section: Construction Of Ionomersmentioning
confidence: 71%
“…The reason could be the presence of nmsized pores within the bers by the extraction of PAA carrier polymer-trapped water via capillary condensation, showing a similar voltage trend to PCL electrodes. 30 This suggests that although NFCL has different pore distributions from PCL, the difference in pore distribution did not inuence the cell performance as expected. It demonstrates a weak inuence of the nanober mat pore structure on performance, consistent with the conclusion drawn from LCD results.…”
Section: Construction Of Ionomersmentioning
confidence: 71%
“…The ethanolamine (MEA)s with Nafion in salt form (Na+, Li+, or Cs+ as sulfonic acid counterion) were prepared by Waldrop et al They showed little or no change in maximum power density when the relative humidity (RH) of the feed gas was lowered from 100% to 40%, while the eMEAwith H+-Nafion/peroxyacetic acid (PAA) fibers showed a 33% power loss at 40% RH. The higher power densities at low humidity were attributed to capillary condensation of water in porous fibers with a pore diameter of 1.25 nm or less [115]. On the one hand, the interconnected porous structure of nanofibers enables efficient gas diffusion and transport and provides uniform distribution of reactants and products within the fuel cell [110].…”
Section: Fuel Cell Membrane Electrodesmentioning
confidence: 99%
“…Another approach for generating new battery electrode architectures is nanofiber electrospinning. Over the last decade, fiber mat materials, where the fibers contain particles and a polymer binder, have been prepared and characterized for both fuel cell [24,25] and LIB [26][27][28][29] electrodes with promising results. Self et al, for example, showed that a freestanding nanofiber particle/polymer anode containing Si nanoparticles, poly(acrylic acid) and carbon black (Si/PAA/C) worked well in a Li battery coin cell [27].…”
Section: Introductionmentioning
confidence: 99%